The reduction of vehicular traffic during the Zion Christian Church Easter weekend pilgrimage - Mathebula, Andrew Mabila; Smallwood, John (Organization, Technology and Management in Construction: an International Journal, 2022)
The study investigated the impact of the high volume of vehicular traffic on pilgrims and the community during the Zion Christian Church Easter weekend pilgrimage. The findings indicate that the South African transport planning approach is ossified and divorced from reality. There is a lacuna to address peak traffic challenges during the Easter weekend and the festive season. Notably, the government-led seasonal road safety campaigns, such as “Arrive Alive”, are curiously inadequate to address peak traffic and road accidents challenges in South Africa. The study employed the action research approach by collaborating with the Polokwane Local Municipality (PLM) to come up with lasting solutions to traffic congestion during the Easter weekend. The study found that the vehicular mode of transport was inadequate to cater for the mobility of pilgrims as well as other motorists during Easter weekend. The transport management framework for the PLM and a peak traffic standard were developed as part of the study recommendations. These recommendations augur a shift to transport planning in South Africa.
free